2022
DOI: 10.53730/ijhs.v6ns3.8371
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion index as a predictor of hypotension following subarachnoid block in parturients with non-severe pre-eclampsia undergoing lower segment cesarean section

Abstract: Background and Aims: Perfusion index, which assesses perfusion dynamics is used as a non‑invasive method in spinal anesthesia cases to detect the occurrence of hypotension. A Perfusion Index value after which hypotension is common can be assessed. Methods: In this prospective double-blind observational study, 100 parturients were included. Baseline Perfusion Index was recorded and spinal anesthesia was carried out with Injection bupivacaine 0.5% (hyperbaric), 10 mg at L3 - L4 / L2 - L3 intervertebral space. Fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The maternal age and body weight did not have any correlation with the occurrence of post-spinal hypotension in parturients of our study. However, the study conducted by Xu et al [28] showed maternal age, body weight, and BMI in parturients with post-spinal hypotension were higher compared to those who did not have hypotension.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The maternal age and body weight did not have any correlation with the occurrence of post-spinal hypotension in parturients of our study. However, the study conducted by Xu et al [28] showed maternal age, body weight, and BMI in parturients with post-spinal hypotension were higher compared to those who did not have hypotension.…”
Section: Discussionmentioning
confidence: 90%
“…Regression analysis and ROC curve analysis inferred that a baseline PI cut-off point of 3.5 could be used to recognize parturients vulnerable to hypotension. Likewise, Malavika et al [28] reported a cut-off PI of 4.25 with a sensitivity and specificity of 74.5% and 89.7%, respectively, to detect hypotension in parturients with non-severe pre-eclampsia undergoing LSCS. Xu et al [29] correlated with a high baseline PI of the finger (>3.5) and a low baseline PI of the toe (<2.2) as a predictor of hypotension.…”
Section: Discussionmentioning
confidence: 98%